Picturing self empowerment: a phenomenological study of adolescent girls that self injure involved in phototherapy group work - Briggs, Melissa Marie (Kansas State University, 2013)
The purpose of this phenomenological research study was to describe and to understand the experience of being in a PhotoTherapy group for adolescent females in treatment for self-injurious behaviors. The research question was as follows: (1) What was the essence of the experience of a series of PhotoTherapy group sessions for female adolescents with a history of self-injurious behaviors? After the completion of two semi-structured interviews with 5 participants, the researcher acknowledged the emergence of four themes that expressed the essence of the experience of being a part of a PhotoTherapy group process as an adolescent female in treatment for self-injurious behaviors. The themes were the following: Self, Connection with others, Emotions, Motivations in treatment. These themes developed a description of the interactions, emotions, behaviors and thoughts that occurred throughout the group work process. Self-injury is a complex issue and the literature states a need for creative interventions. The study collaborated the needs in the field of self-injury treatment with the resources available from PhotoTherapy. The study gained perspective and understanding of how the experience of being in a PhotoTherapy group impacted the individual. In mental health and education, counselors can use the data and conclusions from this research to understand the use of PhotoTherapy group work with adolescent girls that self injure. The researcher concludes that counseling professionals have an understanding of creative interventions and the personal experiences endure with the use of creative interventions such as, PhotoTherapy to have a holistic perspective on treatment practices.
Keywords: Phenomenology; PhotoTherapy; Counseling; Self injury; Counseling Psychology (0603); Psychology (0621); School Counseling (0519)